The social commerce handbook : 20 secrets for turning social media into social sales - Marsden, Paul (McGraw-Hill, 2013)
Revealing the secrets to unlocking sales with the Big Five--YouTube; Pinterest; Facebook; Twitter; and LinkedIn; this book distills the real-world experience of successful social commerce businesses--from Apple to Zappos--into 20 secrets for turning Likes into Buys. --